Strategi Komunikasi Pemasaran Penerbit Buku Obelia Di Kota Medan - Fikri Sulaiman; Indira Fatra Deni (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the marketing communication strategy of Obelia book publishers in their bookstores in increasing product sales and maintaining the existence of printed books amidst the rise of technological developments that have given birth to the latest information tools in the form of the internet and electronic books (E-books). This study uses a qualitative approach, and the types and data of this research are descriptive. This study uses the theory of marketing communication mix or Marketing Mix, namely advertising, sales promotion, public relations, direct marketing and personal selling. Researchers conducted in-depth interviews with the founder who is also the owner of the Obelia bookstore. The researcher made direct observations in the field and also collected data from previous studies as a reference. The results of this study indicate that the application of Marketing Mix as a marketing communication strategy for Obelia book publishers in Medan is considered effective.